The term structure of sovereign credit default swap and the cross‐section of exchange rate predictability. (22nd December 2019) - Calice, Giovanni; Zeng, Ming
Abstract: We provide novel evidence on exchange rate predictability by using the term premia of the sovereign credit default swap (CDS). Using a sample of 29 countries, we find that the sovereign CDS term premia significantly predict the exchange rates out‐of‐sample. On average, a steeper CDS spread curve for a country predicts its currency appreciation against the U.S. dollar (USD). Empirically, although the sovereign CDS level mainly reflects global risk, the information in the term premia of the sovereign CDS spreads reveals country‐specific risk. Notably, the predictive power of the term premia is robust after controlling for the sovereign CDS level and other conventional global macroeconomic and financial factors. Further analysis shows that the information in the sovereign CDS term premia is also helpful for forecasting international stock market returns.